2021
DOI: 10.1186/s12944-021-01515-8
|View full text |Cite
|
Sign up to set email alerts
|

PGLYRP2 as a novel biomarker for the activity and lipid metabolism of systemic lupus erythematosus

Abstract: Background To assess the value of peptidoglycan recognition protein 2 (PGLYRP2) in assessing the disease activity and lipid metabolism in patients with systemic lupus erythematosus (SLE). Methods SLE patients with stable disease (n = 15), active lupus nephritis (LN) (n = 15) and neuropsychiatric systemic lupus erythematosus (NP-SLE) (n = 15) admitted to Northern Jiangsu People’s Hospital (Jiangsu, China) in 2019–2020 were recruited. In addition, vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(21 reference statements)
0
4
1
Order By: Relevance
“…Of interest, a recent study also showed a positive correlation between PGLYRP2 and ApoB/A1 in patients with systemic lupus erythematosus (SLE), which suggested a potential role of PGLYRP2 in the dyslipidaemia and cardiovascular disease risks in SLE patients. 27 In the present study, no association was found between Q96PD5 and the lipid species differentially identified among groups (TG 48:0), but Q96PD5 was shown to be significantly related to A6XND0, whose gene expression (IGFBP3) was previously related to lipid metabolism. 28 In serum, IGFBP-3 is the most abundant protein of the IGFBP family that functions in an IGF-dependent (delivery of IGF and activation of IGF downstream signalling) manner, as well as in an IGF-independent (interaction with proteins) manner.…”
Section: Discussioncontrasting
confidence: 70%
“…Of interest, a recent study also showed a positive correlation between PGLYRP2 and ApoB/A1 in patients with systemic lupus erythematosus (SLE), which suggested a potential role of PGLYRP2 in the dyslipidaemia and cardiovascular disease risks in SLE patients. 27 In the present study, no association was found between Q96PD5 and the lipid species differentially identified among groups (TG 48:0), but Q96PD5 was shown to be significantly related to A6XND0, whose gene expression (IGFBP3) was previously related to lipid metabolism. 28 In serum, IGFBP-3 is the most abundant protein of the IGFBP family that functions in an IGF-dependent (delivery of IGF and activation of IGF downstream signalling) manner, as well as in an IGF-independent (interaction with proteins) manner.…”
Section: Discussioncontrasting
confidence: 70%
“…In PMR, C3 may contribute to the inflammatory cascade leading to symptoms. Last, PGLYRP2 recognizes bacterial peptidoglycan, playing a role in innate immunity by modulating the immune response to bacterial infections [35]. In addition to its role in promoting inflammation in response to bacterial infections, PGLYRP2 has anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…Immunometabolism is now considered to play a key role in the pathogenesis of SLE 9,10 . Altered expression of genes controlling metabolism, such as those regulating mitochondrial function, lipid metabolism, and anaerobic glycolysis, has been documented in immune cells of SLE patients or murine lupus models, contributing to the disorder immune status [11][12][13][14] . Growing studies have illustrated that metabolites do not only act as intermediates in metabolic processes but also function as critical regulatory molecules in signal transduction 15 .…”
Section: Introductionmentioning
confidence: 99%